Overview of sea conservation policies in Brazil and social and environmental impacts in the context of the COVID-19 pandemic (Research, Society and Development, 2021)
The ocean and its areas of influence are fundamental environments for life on the planet, harbor ample biodiversity and are the basis of support for many vulnerable families and communities, which justifies the implementation and effectiveness of laws and policies for the conservation of marine resources throughout the world. With the pandemic caused by the new coronavirus, many impacts have intensified in these environments, which emphasizes the importance of research that considers these effects and the political scenario in which the pandemic erupted. The objective of this discussion was to evaluate the social and environmental impacts associated with the resources of the sea, verifying the effectiveness of public policies and highlighting the importance of social inclusion, environmental education and shared responsibility. The study area was the Brazilian coast and the research methodology was based on the analysis of secondary data, analysis of official reports and documents, as well as a qualitative bibliographic review of scientific articles, presenting comparisons and interdisciplinary discussions between Brazil and other countries. in order to build a narrative review on the subject, presenting hypotheses for improvements in the post-pandemic scenario. The study reveals that there is a large gap between theory and practice with regard to sea conservation policies, which is enhanced by the political crisis in Brazil and its social, economic and environmental effects, generating impacts and externalities that affect national interests and international. It is concluded that, in the post-pandemic scenario, there will be a great need for joint actions to mitigate the intensified impacts of the pandemic, and it is up to the government to support the most affected and seek to ensure the practical effectiveness of the sea. conservation policies and effective environmental education actions.